Analysis of energy-matching performance and suitable users of conventional CCHP systems coupled with different energy storage systems. (15th November 2019) - Feng, Lejun; Dai, Xiaoye; Mo, Junrong; Shi, Lin
Highlights: Dimensionless matching parameters and scenarios are established. Capacity sizing methods for different system configurations are proposed. The suitable energy storage that coupling with CCHP systems is analysed. The suitable user scopes for different system configurations are calculated. Abstract: An energy storage system is deemed to be an effective way to improve the energy mismatch between the provision of systems and users' demands for combined cooling, heating, and power systems (CCHP). Hence, instead of the case study, dimensionless energy-matching parameters, energy-matching map, and nine universal energy-matching scenarios are proposed to measure the loads disparity between users' demands and the provision of CCHP system when coupled with thermal energy storage system, electric energy storage system, or the hybrid energy storage system, respectively. Then based on the energy-matching relations, the capacity sizing method and suitable user scopes are discussed to find the suitable energy storage system for CCHP systems in different energy-matching scenarios. The results indicate that if the system coupling with electric or thermal energy storage system, the capacity of the CCHP system can be installed in users' average electric or thermal energy demand, however, if the system coupling the hybrid energy storage system, the installed capacity can be summarized into two different situations based on the energy-matching relations. Meanwhile, thermal energy storage system is found to be more applicable when the heating load is dominant and greater energy saving would be achieved when the surplus electricity can be sold back to the Gird. Compared to the conventional CCHP systems, the systems in hot climate zones showed significant performance improvements than in cold climate zone when coupled with energy storage systems. Moreover, suitable users' boundaries in winter or cold climate zones are found to be larger than that in summer or hot climate zones, and a larger installed capacity will contribute to a wider suitable user scope. Finally, a sensitivity analysis is conducted to reveal the influence rules of the key parameters.